The impact of the ileoanal pouch on female fertility in ulcerative colitis: A systematic review and meta‐analysis. (8th April 2022) - Sriranganathan, Danujan; Poo, Stephanie; Segal, Jonathan P.
Abstract: Aim: Ileal pouch–anal anastomosis is a restorative option for patients with ulcerative colitis (UC) requiring surgery. The primary outcome of this study was the relative risk of infertility in women with UC undergoing restorative proctocolectomy (RPC) compared to the same patients before undergoing RPC. Infertility was defined as the inability to conceive after 1 year of regular sexual intercourse without contraception. Methods: A systematic review and meta‐analysis were performed to include all relevant articles from 1946 from MEDLINE, Embase and Cochrane Central Register of Controlled Trials. Studies included reported on the fertility rate of a cohort with UC and also reported the rate after RPC in those within the cohort who underwent surgery. This study was registered on PROSPERO (CRD42021259745). Results: Thirteen studies met the inclusion criteria and accounted for 793 patients pre‐pouch and 802 post‐pouch. The mean and median age of the patients at analysis was 36.8 and 32.7 years respectively; and the median duration of follow‐up following ileal pouch–anal anastomosis was 110.4 (68–139) months. Our results highlight that following RPC the relative risk of infertility is 4.17 (95% CI 1.99, 8.74) compared with patients before RPC who had UC. Conclusions: The findings of this meta‐analysis provide an update on a previous meta‐analysis published over a decade ago and results remain congruent. This suggests that despite advancements in surgical techniques the risk to fertility remains similar to a decade ago. However, further high quality studies are needed to try and decipher independent risk factors associated with a decrease in infertility.